2014
DOI: 10.1242/jcs.157024
|View full text |Cite
|
Sign up to set email alerts
|

DAPK-HSF1 interaction as a new positive feedback loop for TNF-induced apoptosis in colorectal cancer cells

Abstract: Death-associated protein kinase (DAPK) is a serine-threonine kinase with tumor suppressor function. Previously, we demonstrated that tumor necrosis factor (TNF) induced DAPK-mediated apoptosis in colorectal cancer. However, the protein-protein interaction network associated with TNF-DAPK signaling still remains unclear. We identified HSF1 as a new DAPK phosphorylation target in response to low concentrations of TNF and verified a physical interaction between DAPK and HSF1 both in vitro and in vivo. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…However, there is now increasing evidence from a number of biological systems that HSF1 is important for diverse “non-stress” conditions including development [26, 40], energy metabolism [27], programmed cell death [41, 42] and carcinogenesis [28, 43]. For these non-heat shock conditions, the transcriptomes regulated by HSF1 are distinct from that of acute heat shock [26, 40].…”
Section: Hsf1 Directs Transcriptional Programs That Are Uncoupled Fromentioning
confidence: 99%
“…However, there is now increasing evidence from a number of biological systems that HSF1 is important for diverse “non-stress” conditions including development [26, 40], energy metabolism [27], programmed cell death [41, 42] and carcinogenesis [28, 43]. For these non-heat shock conditions, the transcriptomes regulated by HSF1 are distinct from that of acute heat shock [26, 40].…”
Section: Hsf1 Directs Transcriptional Programs That Are Uncoupled Fromentioning
confidence: 99%
“…DAPK can be transcriptionally inhibited by the pro-inflammatory transcription factors STAT3 and NFκB ( 16 , 31 , 32 ). In addition, DAPK mRNA expression can be triggered by p53 ( 33 ), C/EBP-β ( 34 ), HSF1 ( 35 ), and SMAD ( 36 ). Whereas C/EBP-β binding depends on IFNγ exposure, the binding of SMAD to the corresponding motifs is triggered by TGF-β.…”
Section: Regulation Of Dapkmentioning
confidence: 99%
“…Of note, several studies reported that DAPK is crosslinked with TNF-receptor signaling and NF-κB activation providing further evidence for a potential therapeutic importance of DAPK in IBD. However, it was demonstrated that DAPK can process apparently opposing roles when either inhibiting or promoting inflammation ( 16 , 35 , 68 , 72 74 ). Thus, further analyses with careful characterization of cell type specific actions and context-dependent influences are needed before DAPK might be considered a therapeutic target candidate in IBD.…”
Section: Immunology and Inflammatory Responses Associated With Ibdmentioning
confidence: 99%
“…This involves cytotoxic responses to tumors and a consequent increase in the carcinogenesis and metastasis 22, 23. Elevated plasma and tissue levels of TNF-α observed in obesity leading to the establishment of constant inflammatory state that increases the risk of colon cancer development 24, 25. APN is considered to have beneficial antineoplastic effects, which are believed to be due to anti-proliferative, anti-inflammatory effects, along with antagonizing insulin resistance 26.…”
Section: Introductionmentioning
confidence: 99%